The Values of Moderate Theology in Understanding Hadith: Insights from Indonesia - Baharuddin, Mochammad Achwan; Priyanto, Aris; Khotimah, Khusnul; Fauziani, Sifa; Syafik, Muhammad (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2025)
This study aims to examine moderate theology in understanding the Prophet's hadith especially the tolerance hadith narrated by Ahmad. This article aims to reveal the phenomenon of theological studies developing in universities and Islamic boarding schools, which are centres of Islam in Indonesia. The methodology used is a case study with a qualitative approach, involving questionnaires, interviews, and documentation of students and caregivers of partner pesantren state Islamic University K.H. Abdurrahman Wahid Pekalongan. The results showed that the understanding of the hadith of tolerance plays an important role in shaping inclusive and moderate attitudes among santri. The hadith is applied as a foundation to reject extremism, promote interfaith dialog, and support harmony in diversity. Moreover the understanding of the universality of Muhammad's message in partner pesantren strengthens religious moderation in local and global contexts. This study contributes to the phenomenon of comprehensive hadith interpretation as a moderate theological basis for Muslims.